Polarisation and source structure of solar stationary type IV radio bursts - Salas Matamoros, Carolina (2020)
The reconfiguration of the magnetic field during and after a coronal mass ejection (CME) may be accompanied by radio emission from non-thermal electrons. In particular, stationary type IV bursts (also called storm continua) are emitted by electrons in closed magnetic configurations usually located in the wake of the outward-travelling CME. Although stationary type IV bursts, which stand out by their long duration (up to several hours) and strong circular polarisation, have been known for more than fifty years, there have been no systematic studies since the 1980s. In this work we use the data pool of the Nançay Radioheliograph together with white-light coronagraphy, EUV imaging and magnetography from the SoHO, Proba2, SDO and STEREO spacecraft to revisit the source structure and polarisation of a sample of seven well-defined stationary type IV bursts at decimetre-to-metre wavelengths. The radio sources are most often found in one leg, in one case both legs, of the magnetic flux rope erupting into the high corona during the CME. The cross-correlation of the brightness temperature time profiles in the event with sources in both legs implies that the radiating electrons have energies of a few tens of keV. Comparison with the magnetic field measured in the photosphere and its potential extrapolation into the corona shows that the radio emission is in the ordinary mode. This result was inferred historically by means of the hypothesis that the magnetic field orientation in the radio source was that of the dominant sunspot in the parent active region. This hypothesis is shown here to be in conflict with noise storms in the same active region. It is confirmed that the polarisation of stationary type IV continua may be strong, but is rarely total, and that it gradually increases in the early phase of the radio event. We find that the increase is related to the gradual disappearance of some weakly polarised or unpolarised substructure, which dominates the first minutes of the radio emission.